Biodiversity hotspots and Ocbil theory - Hopper, Stephen D.; Silveira, Fernando A. O.; Fiedler, Peggy L. (Plant and soil, 2016)
BACKGROUND: Ocbil theory aims to develop hypotheses explaining the evolution and ecology of, and best conservation practices for, biota on very old, climatically buffered, infertile landscapes (Ocbils). SCOPE: This paper reviews recent multi-disciplinary literature inspired by or reacting to aspects of Ocbil theory and discusses how it can assist conservation in biodiversity hotspots. CONCLUSIONS: Ocbils occur in at least 12 out of 35 known terrestrial hotspots, but also in other biologically significant sites. Most evidence comes from the Southwest Australian and Greater Cape Floristic Regions, South America’s Pantepui, and the Campo Rupestre of Brazil, though predictions of the theory have been corroborated in 22 sites across South America, Western and Eastern Africa, Southern Asia, and Oceania. Most hypotheses have been corroborated, indicating that Ocbil theory has survived largely intact after 6 years of independent scientific critique, quantitative experimentation, and development. The theory also has been extended to allow identification and characterization of OCBISs (old, climatically-buffered, infertile seascapes), and OCFELs (old, climatically-buffered, fertile landscapes). We illustrate that the principles of Ocbil theory are key to conservation of biodiversity at global scale and provide new directions for research that can improve the theoretical and practical contributions of Ocbil theory.